FUNCTIONAL RECOVERY IN PATIENTS WITH ACUTE ISCHEMIC STROKE AND ITS DEPENDENCE ON THE BLOOD PRESSURE VARIABILITY - Cherenko, T. M.; Heletyuk, Yu.L. (The Ukrainian Scientific Medical Youth Journal, 2018)
Objective - to investigate the association between functional recovery in patients with acute ischemic stroke and arterial hypertension, daily blood pressure (BP) monitoring and its variability. Materials and methods. One hundred fifty patients with initial ischemic stroke and history of arterial hypertension have been examined: 74 (49.3%) women and 76 (50.7%) men with mean age of 67.4±0.7 years. Neurological deficit was evaluated by NIHSS scale, functional outcome – by Barthel index. The diagnosis of hypertension was based on the results of clinical, instrumental examination and medical documentation. Blood pressure daily monitoring was applied from the admission and every 4 hours during 6 days of acute stroke period. We studied mean values of SBP, DBP, maximum values of SBP and DBP, the variability of blood pressure (SD), counted for SBP and DBP. Statistical analysis of the results was performed using the statistical analysis IBM SPSS Statistics Base v.22. Results. The degree of functional recovery in patients with history of hypertension in the acute stroke period significantly correlated with the severity of hypertension (r=0.351), its duration (r=0.426) and degree of neurological deficiency at discharge: r=0.739, p=0.001. The most significant association between the parameters of daily blood pressure monitoring and functional dependence at the end of an acute period was established: between SD SBP and the Barthel index for 1 day, 1-3 days and 1-6 days: r =-0427, r =-0.551 and r =-0.515, respectively; SD DBP significantly correlated only in the interval from 1 to 3 days (r=0,550). Single-factor regression analysis has found the association between the functional defect degree in patientswith acute stroke at discharge and systolic blood pressure variability over a period of 1-3 days, R2 = 0.304. Conclusions. The effectiveness of functional recovery depends on the systolic blood pressure variability over a period of 1-3 days after stroke.